A bibliometric overview of the International Journal of Strategic Property Management between 2008 and 2019 - Zhou, Wei; Xu, Zeshui; Zavadskas, Edmundas Kazimieras (International Journal of Strategic Property Management, 2019)
The International Journal of Strategic Property Management (IJSPM) is an interdisciplinary journal which provides a forum for a broad range of strategic property management research. The topics such as asset and facilities management, property policy, risk management, residential property value enhancement, and housing finance are included in the scope of the IJSPM’s investigation. The aim of this study is to provide a bibliometric analysis of the papers published by the IJSPM which is collected in the well-known Social Science Citation Index database and analyse the current status and the emerging trends of the research outputs in the IJSPM with some broadly utilized as well as diversely designed indicators. By analysing the annual publication distribution, the citation structure, the co-citation and cooperation networks, and the influential contributors on the aspects of specific countries/regions, institutions, cited journals, and authors, the status quo of the IJSPM publications is presented. Also, the emerging trends are explored through the analyses of timeline view and burst detection. We make the contributions in terms of visualizing the complex and significant results based on the objective and quantitative data. This paper assists researchers with an understanding of the development of the IJSPM, which gives useful information for further researches and submitting works.